Dual mimic enzyme properties of Fe nanoparticles embedded in two-dimensional carbon nanosheets for colorimetric detection of biomolecules. Issue 1 (7th December 2022) - Wang, Jie; Zhao, Chenglong; Zhou, Feijin; Lu, Hui; Huang, Zhenhong; Yao, Cheng; Song, Chan
Abstract : Taking advantage of their dual enzymatic activity, Fe@CNs were employed in the construction of a universal sensing platform for the detection of biomolecules such as GSH, H2 O2, and glucose. Abstract : The development of novel nanozymes is of great importance for the efficient analysis of biomolecules such as H2 O2, glucose, and antioxidants in the diagnosis of some diseases. Herein, novel nanozymes based on Fe nanoparticles (NPs) encapsulated in 2D carbon nanosheets (denoted as Fe@CNs) were constructed and employed in the field of biosensing. Notably, Fe@CNs have intrinsic dual mimic enzyme properties. The colorless colorimetric substrate 3, 3′, 5, 5′-tetramethylbenzidine (TMB) can be oxidized by Fe@CNs as oxidase- and peroxidase-like nanozymes, respectively. The generation of the oxidation state TMB (oxTMB) resulted from the presence of reactive oxygen species (ROS) which were produced by the catalytic decomposition of the dissolved oxygen or H2 O2 . Thus, a simple colorimetric biosensor was proposed to detect glutathione (GSH), H2 O2, and glucose. In addition, the Fe@CN-based nanozymes also have excellent reusability in enzymatic catalysis. After separating from the sensing systems, Fe@CNs can be reused in other catalytic processes. This colorimetric method could be used as a universal sensing platform for the detection of antioxidants and H2 O2 -related bioanalysis. This work broadens the application of novel nanozymes in biosensing.